An Appraisal of the Compatibility of Pardon Decisions with Obligations of International Law - Ngwoke, Rita Abhavan; Eruteya, Ugiomo; Oyinloye, Tawakaltu Queen (Acta Universitatis Danubius. Juridica, 2024)
This paper examines the challenges of aligning pardon decisions for grave international offenses, such as war crimes and genocide, with international law standards, focusing on their impact on justice, accountability, and human rights. Building on existing research regarding the tension between national sovereignty and international legal obligations, it references key treaties like the International Covenant on Civil and Political Rights, the Convention Against Torture, the Rome Statute, and the Geneva Conventions. Utilising a doctrinal research methodology, the paper conducts a comparative analysis of case studies from various jurisdictions. The findings reveal that while pardons can aid national reconciliation, they often conflict with international obligations, undermining principles of justice and accountability. This study draws attention to the need for blending international human rights and humanitarian law principles with domestic pardon procedures, suggesting legislative reforms and increased international collaboration to ensure that pardon decisions uphold international legal standards. The paper contributes to the discourse on balancing state sovereignty with international legal obligations, advocating for stronger integration of international standards in domestic practices.